1980
DOI: 10.1111/1365-3040.ep11581825
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparisons of five N2‐fixing Azolla‐Anabaena associations, I. Optimization of growth conditions for biomass increase and N content in a controlled environment*

Abstract: Biomass increase, C and N content, C2H2 reduction, percentage dry weight and chlorophyll a/b ratios were determined for clones of Azolla caroliniana Willd., A.filiculoides Lam., A. mexicana Presl., and A. pinnata R.Br. as a function of nutrient solution, pH, temperature, photoperiod, and light intensity in controlled environment studies. These studies were supplemented by a glasshouse study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The growth rates measured are in the range reported in literature 32 , 34 37 . However, higher RGRs may be obtained when growing Azolla under optimal conditions using synthetic media in aquaculture 1 , 38 . Self-crowding may also result in lower RGRs of the fern, however, during the experiment the biomass was lower than the self-crowding threshold of 2 kg FW m −2 and was therefore not responsible for the biphasic growth response 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The growth rates measured are in the range reported in literature 32 , 34 37 . However, higher RGRs may be obtained when growing Azolla under optimal conditions using synthetic media in aquaculture 1 , 38 . Self-crowding may also result in lower RGRs of the fern, however, during the experiment the biomass was lower than the self-crowding threshold of 2 kg FW m −2 and was therefore not responsible for the biphasic growth response 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation of events is conid complement of phy-sistent with the findings in a recent study of the ultrastructural allophycocyanin (APC) ontogeny of the leaf cavity trichomes and our current underintact main stem axes; standing of this symbiosis (3,14). is based on three to five A prior study showed that the energy absorbed by PBP effec-D. (20).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses were conducted using both individual leaves and pairs of leaves sequentially dissected from the axes beginning with the apical segment. Triplicate samples of single leaves, and pooled leafpairs of the same developmental stage, were placed in 1 ml vials containing 0.25 ml of N-free growth medium (20) and allowed to equilibrate at 25°C in the light, 200 ,E.m-2-ss', for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations